ROMANIAN COMPANIES DILEMMAS - BUSINESS REENGINEERING OR KAIZEN - MIHAELA GHICAJANU (Annals of the University of Petrosani: Economics, 2011)
This paper presents an analysis of two American and Japanese management strategies, the reengineering and Kaizen strategies, which can be used successfully by the Romanian companies, too. Reengineering is the fundamental rethinking and radical redesign of business processes to achieve dramatic improvements in critical contemporary measures of performance such as cost, quality, service and speed. Kaizen is a philosophy of life that addresses to the best who want to be more and better. It is a process of improvement that never ends and it results in many advantages. The Japanese leadership model has shown that progress in small steps, but fast, reliable and leads to long-term wins. Kaizen method, implemented in Romania, too, has brought to people satisfaction and more money in their pocket.